Novel current controlled differential-input buffered output active element and its application in all-pass filter - Khateb, Fabian; Dabbous, Salma Bay Abo; Kumngern, Montree; Kulej, Tomasz (My University, 2015)
This paper presents a novel high-performance first-order voltage-mode all-pass filter based on single active element and single grounded capacitor. The filter provides high-input and extremely low output impedances with possibility of electronic tuning of its natural frequency. The active element used in the filter design is novel and named current controlled differential-input buffered output (CC-DIBO) where the intrinsic resistances of its input current terminals can be controlled independently by external balancing bias currents. The proposed CC-DIBO element has current and voltage terminals appearing on both of its input and output; hence it is suitable for voltage-, current- and mixed-mode applications. The SPICE simulation results of the proposed filter properties using the 0.18μm CMOS technology from TSMC are also presented.
Keywords: All pass-filter; current controlled active elements; voltage-mode